Mestre Cheiroso chegou: percursos formativos do brincante Augusto Barreto - Santos, Gustavo Floriano dos (2023)
Mamulengo de Cheiroso is a Sergipe theater group that resists the challenges of time and remains active in contemporary. Affirming its artistic trajectory for forty-four years, the group has in the puppet the spokesperson of a poetics and an aesthetic of its own, inspired by the universe of dances, songs and craftsmanship, as well as in the popular circus dramas. In the construction of this trajectory, among so many actors, directors and playwrights who have passed through the group, there is a fundamental presence that is Augusto Barreto: master, craftsman, puppeteer and cultural manager of Mamulengo de Cheiroso. Given the significant presence of Augusto Barreto, for the construction and maintenance of this group, the guiding question of this research asks: How was the artistic and pedagogical training of the playful Augusto Barreto considering the theatrical carpentry of Mamulengo de Cheiroso? Tracing the backbone of this dissertation, I chose as a methodological foundation, Oral History (MEIHY, 2000 and MEIHY and HOLANDA, 2013), I understand that this is the compass that corroborates the researched field, from the premise of "seeing, hearing and attesting" (MEIHY, 2013), witnessed by the research collaborators, about the relationships with the investigated character.